Transcranial Doppler: Does Addition of Blood to Agitated Saline Affect Sensitivity for Detecting Cardiac Right‐to‐Left Shunt?. Issue 8 (20th April 2016) - Mojadidi, Mohammad Khalid; Zhang, Lili; Chugh, Yashasvi; Eshtehardi, Parham; Hovnanians, Ninel; Gevorgyan, Rubine; Mojaddedi, Sanaullah; Nezami, Nariman; Zaman, Muhammad Omer; Rafique, Asim; Villablanca, Pedro A.; Tobis, Jonathan M.
Abstract : Background: Transcranial Doppler (TCD) with agitated saline has been shown to be an alternative for the detection of right‐to‐left shunts (RLS) with similar diagnostic accuracies as transesophageal echocardiography (TEE). It is hypothesized that the addition of blood to agitated saline increases the sensitivity of TCD for the detection of RLS. The aim of this meta‐analysis was to determine whether agitated saline with blood increases the sensitivity of TCD for the detection of RLS compared to agitated saline alone and other contrast agents. Method: A systematic review of Medline, Cochrane, and Embase was performed to look for all prospective studies assessing intracardiac RLS using TCD compared with TEE as the reference; both tests were performed with a contrast agent and a maneuver to provoke RLS in all studies. Results: A total of 27 studies (29 comparisons) with 1, 968 patients met the inclusion criteria. Of 29 comparisons, 10 (35%) used echovist contrast during TCD, 4 (14%) used a gelatin‐based solution, 12 (41%) used agitated saline, and 3 (10%) utilized 2 different contrast agents. The addition of blood to agitated saline improved the sensitivity of TCD to 100% compared to agitated saline alone (96% sensitivity, P = 0.161), echovist (94% sensitivity, P = 0.044), and gelatin‐based solutions (93% sensitivity, P = 0.041). Conclusion: The addition of blood to agitated saline improves the sensitivity of TCD for the detection of RLS to 100% when compared to other conventional contrast agents; these findings support the addition of blood to agitated saline during TCD bubble studies.